The urgence of safe house for children victims of sexual violence in Aceh from legal political perspective - Roslaili, Yuni; T., Ainal Yunarti (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2022)
Cases of sexual violence are increasingly occurring in Indonesia, including in Aceh. Therefore, the existence of a safe house is seen very necessary and doing research on it is very important. However, in the context of Aceh, it becomes more important and interesting in relation to the regulation of the implementation of Islamic law. This paper discusses the existence of a safe house for victims of sexual violence in a sharia country, what if it is associated with the perspective of legal politics and maqasid al-syariah. This study used qualitative research using empirical juridical research methods, namely a field research that examines the applicable legal provisions and what happens in reality in society. The result of the study showed that the existence of safe houses in Aceh was very crucial. However, until then, Aceh only had two safe houses, although actually not too worthy to be called a definitive safe house. Normatively, there were many laws and qanuns having been made, but it seems that there was little political will and commitment from the authorities, even though in a syar'i perspective, the existence of safe houses in the perspective of maqasid al-syariah as dharuriyyah side is very important from Islamic perspective.